In situ x-ray diffraction measurements of the c/a ratio in the high-pressure epsilon phase of shock-compressed polycrystalline iron - Hawreliak, J; El-Dasher, B; Lorenzana, H; Kimminau, G; Higginbotham, A; Nagler, B; Vinko, S; Murphy, W; Whitcher, T; Wark, J; Rothman, S; Park, N (2011)
The structure of laser-shock-compressed polycrystalline iron was probed using in situ x-ray diffraction over a pressure range spanning the α-ε phase transition. Measurements were also made of the c/a ratio in the ε phase, which, in contrast with previous in situ x-ray diffraction experiments performed on single crystals and large-scale molecular dynamics (MD) simulations are close to those found in high-pressure diamond anvil cell experiments. This is consistent with the observation that significant plastic flow occurs within the nanosecond time scale of the experiment. Furthermore, within the sensitivity of the measurement technique, the fcc phase that had been predicted by MD simulations was not observed. © 2011 American Physical society.